History Of Education Of Fine Arts In Uzbekistan - Bakhriddinov Madyorbek Zainobiddin Ogli (Euro Asian Journal Publishing, 2024)
In this article, the history of visual arts education in Uzbekistan, the fact that our ancestors have been engaged in drawing pictures carved on rocks or painted in different colors in our country, have been extensively covered.
Keywords: Natural paints; Karatepa; temples; Avesta